Characterization of particulate matter formed during sewage sludge pyrolysis. (15th July 2018) - Hac Ko, Jae; Wang, Jingchen; Xu, Qiyong
Highlights: PM generated during sewage sludge pyrolysis varied with temperature rise. The composition of PM varied with temperature rise. PM generation was promoted by increasing inert gas flow rate. PM generation was high during pyrolysis with high volatile content sludge. Abstract: Particulate matter (PM) formation during sludge pyrolysis was investigated under different operating conditions. The impact of inert gas flow rate, heating rate, and sludge types on PM generation was examined. PM generated during sewage sludge pyrolysis varied with tested conditions and ranged from 1.14 wt% to 6.33 wt%. A PM characterization study revealed that carbon content decreased, but oxygen, sulfur, and phosphorus contents increased with increasing temperature. It was considered that the PM formation mechanism varied with different temperature ranges. The increase of inert gas flow and volatile content of sewage sludge promoted PM generation. The formation of PM could be reduced by a low inert gas flow rate, and with lower volatile content of sewage sludge.